Can database-level MEDLINE exclusion filters in Embase and CINAHL be used to remove duplicate records without loss of relevant studies in systematic reviews? An exploratory study - Zahra Premji; Heather Ganshorn (Journal of the Canadian Health Libraries Association, 2020)
Objective: To investigate whether using database filters to remove MEDLINE results within Embase (OVID) and CINAHL (EBSCO) would result in fewer records, without leading to any loss of studies included in the final review.